Preparação de nanopartículas de prata e seus compósitos com polímeros condutores m moldes flexíveis e líquidos iônicos - Correa, Cintia Marques [UNIFESP] (2013)
Ionic liquids (IL), liquid salts at room temperature, show self-organization due to the electrostatic interactions between their ions and the van der Waals among the alkyl chains of the cationic species, being classified as structure directing agent for nanomaterials and polymers synthesis. This works will present the preparation, studying some synthetic parameters (different molar ratio between oxidant/monomer (K) and oxidant agent concentration (C)) of silver and two conductive polymers composites, called polyaniline (PANI), and polypyrrole (PPY), using as structure directing agent two ionic liquids, 1-butyl-3-methylimidazolium (BMIM) bis(trifluoromethanesulfonyl)imide (Tf2N) and tetrafluoroborate (BF4) and silver salts soluble in the LI . With the variation of the synthetic parameters was possible to evaluate their influence on the composites properties. PANI/Ag composites were obtained successfully and all characterizations confirmed the presence of PANI in the emeraldine form and metallic silver in nanoscale. Depending on the used conditions (K and C) electrical conductivity values ranged from 55 until 830 S.cm-1, which are higher than those of pure PANI. PPY/Ag composite exhibited electrical conductivity value around 10-1 S.cm-1. Silver nanoparticles were also prepared from Ag+ reduction using tetrabutylammonium borohydride in different ionic liquids based on imidazolium cations, called 1-butyl-3-methylimidazolium (BMIM) or 1-butyl-2,3-dimethylimidazolium (BMMIM) or 1-methyl-3-octylimidazolium (OMIM) bis(trifluoromethanesulfonyl)imide (Tf2N) and tetrafluoroborate (BF4). Although, nanoparticles have been obtained in all cited ionic liquids, in ionic liquids containing Tf2N. The dispersions showed greater stability than in IL containing BF4. The presence of polyvinylpyrrolidone (PVP) was crucial to increase the stabilization of the nanoparticles and at higher polymer concentration, the higher the nanoparticles stability. The dispersions are viscous and yellow, without precipitates and containing nanoparticles with diameters around 6-12 nm. Finally, tetrabutylammonium citrate was used for the preparation of silver nanoparticles, acting as both solvent as reducing agent. This method promoted the preparation of silver nanoparticles dispersions in the absence of any stabilizing agent, highly concentrated and containing nanoparticle with diameter of 2-6 nm.